1986
DOI: 10.1029/ja091ia02p01661
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric and thermospheric response over Millstone Hill to the May 30, 1984, annular solar eclipse

Abstract: The National Center for Atmospheric Research (NCAR) thermospheric general circulation model (TGCM) is used to calculate the time‐dependent thermospheric response to the May 30, 1984, annular solar eclipse. The path of maximum obscurity begins at sunrise in the Pacific Ocean near 2°N and 135°W. It moves northeastward, passing across central Mexico, the eastern United States, and then the Atlantic before ending near 28°N and 4°E in Algeria. The area of the partial shadow is relatively large, and the total solar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 36 publications
6
48
1
Order By: Relevance
“…3, the modelled results suggest that there is a larger decrease in NmF1 than in NmE, which is in accord with the measured results. A similar result was reported by Roble et al (1986). Both measured and modelled results reveal that during the eclipse the response of electron density in the F1 layer is larger than that in the E layer.…”
Section: Ionospheric Response At the Time Of Maximum Eclipsesupporting
confidence: 77%
See 2 more Smart Citations
“…3, the modelled results suggest that there is a larger decrease in NmF1 than in NmE, which is in accord with the measured results. A similar result was reported by Roble et al (1986). Both measured and modelled results reveal that during the eclipse the response of electron density in the F1 layer is larger than that in the E layer.…”
Section: Ionospheric Response At the Time Of Maximum Eclipsesupporting
confidence: 77%
“…There are some studies on the ionospheric response to solar eclipse on the basis of the numerical simulations in the past (e.g. Stubbe, 1970;Roble et al, 1986;Müller-Wodarg et al, 1998;Boitman et al, 1999;Liu et al, 1999;Korenkov et al, 2003a, b). However, for the variations of solar radiation during a solar eclipse, they only considered the occultation of the photosphere, i.e.…”
Section: Ionospheric Model and Solar Radiation During An Eclipsementioning
confidence: 99%
See 1 more Smart Citation
“…The sources of gravity waves were proposed to be the thermosphere where molecular oxygen heating begins (Chimonas, 1970), the stratosphere where ozone layer heating takes place (Fritts and Luo, 1993;Zerefos et al, 2000) and the troposphere where water vapor IR absorption and ground cooling occurs (Chimonas and Hines, 1971;Chimonas, 1973). Modeling studies supported the idea of eclipse-induced gravity wave generation in the thermosphere (Ridley et al, 1984;Roble et al, 1986;Muller-Wodarg et al, 1998), which is also supported by measurements (Liu et al, 1998;Altadill et al, 2001;Sauli et al, 2006). Zerefos et al (2007) reported waves with periods ranging from 30 to 40 min associated with thermal stratospheric ozone forcing.…”
Section: Introductionsupporting
confidence: 57%
“…Lastly, a source location has been identified in the thermosphere at 170 km altitude due to reduced heating by absorption of extreme ultraviolet solar radiation, based on the analysis of ionosonde measurements (Liu et al, 1998;Altadill et al, 2001;Sauli et al, 2006), while larger periods of about 1 h have also been reported (Altadill et al, 2001). Prior to those observations, the idea of an in-situ thermospheric wave source was highlighted by various modeling studies (Ridley et al, 1984;Roble et al, 1986;Müller-Wodarg et al, 1998).…”
Section: Introductionmentioning
confidence: 99%